Experimental hypothermia by cold air: a randomized, double-blind, placebo-controlled crossover trial - Ane M. Helland; Sigurd Mydske; Jörg Assmus; Guttorm Brattebø; Øystein Wiggen; Haakon K. Kvidaland; Øyvind Thomassen (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Accidental hypothermia is associated with high morbidity and mortality. Research on treatment strategies for accidental hypothermia is complicated by the low incidence and heterogeneous patient population. We have developed a new method for clinical trials of experimental hypothermia, to enable further studies of active rewarming. If cold ambient air is effective as a cooling method, this would mimic the most frequent clinical setting of hypothermic patients and provide a feasible cooling method for field studies. We aimed to induce mild hypothermia in healthy volunteers by exposure to cold ambient air, and tested the hypothesis that drug-induced suppression of endogenous thermoregulation would be required. Methods In a randomized, double-blind, crossover design, 15 healthy volunteers wearing wet clothes were put in a windy climate chamber set to 5 °C. Each participant completed the experimental procedure twice, once receiving active drugs (meperidine and buspirone) and once receiving placebo. The experiments were separated by a one-week wash-out period. Primary outcome was core temperature at termination, defined as 3 h of exposure or 35 °C. The between-groups difference was assessed using analysis of covariance (ANCOVA) with left censoring (Tobit model) and individual random intercept. Secondary outcomes were trajectory of core temperature and reduction of shivering. Results At termination, the active drug vs placebo group differed in temperature by 1.4 °C. With adjustment for the removal of participants reaching 35 °C, the estimated mean difference was 1.7 °C (1.4–2.0, p < 0.001). Shivering was effectively reduced, but not completely inhibited by the drug regimen, and core temperature declined at a rate of − 0.82 °C per hour. Conclusion The novel protocol utilizing cold air as a cooling method and drug-induced suppression of endogenous thermoregulation, is effective and enables future research projects. We have provided suggestions for minor alterations. Trial registration: EudraCT ID 2023–506020-81–00.